The effects of exercise and diet on sex steroids in breast cancer survivors. Issue 8 (29th June 2022) - Brown, Justin C; Sturgeon, Kathleen; Sarwer, David B; Troxel, Andrea B; DeMichele, Angela M; Denlinger, Crystal S; Schmitz, Kathryn H
Abstract : Insufficient physical activity and obesity are associated with an increased risk of cancer recurrence and death in breast cancer survivors. Sex steroid hormones may mediate these associations. This study tested the hypothesis that exercise and diet, as compared to control, favorably change sex steroid hormones. This analysis of data from a subset of participants in a 2 × 2 factorial trial compares 269 postmenopausal breast cancer survivors who were insufficiently physically active and had overweight or obesity and were randomized to one of four treatment groups for 52 weeks: control, exercise alone, diet alone, or exercise plus diet. Secondary sex steroid hormone endpoints included estradiol, sex hormone-binding globulin (SHBG), and testosterone. Treatment effects were quantified using a mixed model for repeated measures. Compared to control, exercise alone did not significantly change estradiol (−1.9%; 95% CI: −12.6, 8.8), SHBG (2.4%; 95% CI: −9.9, 14.6), or testosterone (1.2%; 95% CI: −12.2, 14.5). Compared to control, diet alone did not significantly change estradiol (−7.8%; 95% CI: −17.6, 1.9), SHBG (8.2%; 95% CI: −4.2, 20.6), or testosterone (−0.8%; 95% CI: −13.6, 12.0). Compared to control, exercise plus diet did not significantly change estradiol (−6.3%; 95% CI: −16.3, 3.6), SHBG (8.8%; 95% CI: −4.0, 21.7), or testosterone (−5.3%; 95% CI: −18.0, 7.4). In postmenopausal breast cancer survivors who were insufficiently physically active and had overweight or obesity, randomization to exercise alone, diet alone, or exercise plus diet did not statistically significantly change sex steroid hormone concentrations at week 52.